The great train robbery [videorecording (Blu-Ray)] - Crichton, Michael, 1942-2008; Connery, Sean; Sutherland, Donald, 1935-; Down, Lesley-Anne; Webb, Alan, 1906-1982; Crichton, Michael, 1942-2008 (KL studio classics., 2023)
A "spine-tingling and suavely performed" adventure (The Hollywood Reporter) based on history's first train robbery. Stunningly shot by the great cinematographer Geoffrey Unsworth (2001: A Space Odyssey, Murder on the Orient Express), this "ingenious" (Variety) crime caper delivers mile-a-minute thrills and breathtaking excitement. Connery is Edward Pierce, a master thief who conceives a brilliant plan to steal a fortune in gold bars from a railroad payroll car. But to pull off the most daring heist in history, Pierce must join forces with a safecracker and his beautiful girlfriend in a series of intricately plotted thefts that will test all of their nerve, camaraderie, and larcenous skill.